Evaluating the Effectiveness of Teacher Training Programs on Curriculum Implementation in Indonesian Secondary Schools - Chyntia wongso; Sabrina Rosa Aidia; Muhammad Zanuar Habibi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study assesses the effectiveness of teacher training programs aimed at supporting the implementation of Indonesia's national curriculum reforms in secondary education. Using a mixed-methods approach, the research evaluates teacher perceptions, classroom practices, and student outcomes in schools across different provinces. Results indicate that well-structured training significantly enhances teacher confidence and curriculum delivery, although challenges in program consistency and support mechanisms remain. Policy implications emphasize the need for continuous professional development and localized support to improve curriculum implementation.